2021
DOI: 10.1111/jvim.16252
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of medical dissolution for suspected struvite cystoliths in dogs

Abstract: Background Medical dissolution of struvite uroliths in dogs is commonly recommended, but data on success rates and complications are limited. Objectives To evaluate the efficacy of medical dissolution for suspected struvite cystoliths in dogs. Animals Fifty client‐owned dogs fed a therapeutic dissolution diet, with or without administration of antimicrobials, for treatment of suspected struvite cystoliths. Methods Single institution, retrospective case series. Medical records were reviewed for dogs with at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…While the study investigated the effect of dietary fat content on serum cPLI concentration, this study cannot be extended to infer the effects of high fat diets on the development of pancreatitis. In another study 2/50 dogs receiving a struvite dissolution diet (5.7 g/100 kcal, 26.3% crude fat) were noted to develop pancreatitis 4 . A control group was not used as part of the study design and the basis for a diagnosis of pancreatitis is not reported.…”
Section: Etiology and Potential Risk Factors For Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…While the study investigated the effect of dietary fat content on serum cPLI concentration, this study cannot be extended to infer the effects of high fat diets on the development of pancreatitis. In another study 2/50 dogs receiving a struvite dissolution diet (5.7 g/100 kcal, 26.3% crude fat) were noted to develop pancreatitis 4 . A control group was not used as part of the study design and the basis for a diagnosis of pancreatitis is not reported.…”
Section: Etiology and Potential Risk Factors For Pancreatitismentioning
confidence: 99%
“…High fat diet [2][3][4] Ingestion of unusual food items 5,6 Ingestion of table scraps 5 Ingestion of trash 5 Drugs/toxins L-asparaginase 7,8 Phenobarbital and potassium bromide 9-11a Azathioprine [12][13][14] Potentiated sulfonamides 15 Organophosphates 12,16 Corticosteroids, 12,17b Furosemide 12 Atovaquone/proguanil (Malarone) 18 N-methyl-glucamine (Meglumine), 19b…”
Section: Dietary Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research is therefore needed to further investigate the relationship between naturally occurring renal disease and pancreatitis. Renal and urinary diets are often higher in dietary fat than standard adult maintenance diets, and this could be a contributing factor in this relationship; indeed, 10 dogs in our study were receiving such diets [ 33 ]. However, dietary fat level was not definitively assessed, and as such, this remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although the relative prevalence of different types of canine uroliths has changed over the last 20 years, struvite remains one of the most common canine urolith types encountered, comprising 36% d,l-Methionine in combination with amoxicillin-clavulanic acid successfully dissolves spontaneously occurring infection-induced struvite urocystoliths in dogs: a pilot study to 43% of canine urolith submissions encountered at urolith analysis centers, including the Minnesota Urolith Center. 2,3,4 The majority (95%) of struvite uroliths occur in the lower urinary tract. 1 Most infection-induced struvite uroliths are amenable to medical treatment for dissolution using a diet change to decrease urine concentrations of struvite calculogenic compounds and an antimicrobial agent.…”
mentioning
confidence: 99%